Speaking to body and soul : instructions for the Moravian choir helpers, 1785-1786 - Faull, Katherine M. (University Park, Pennsylvania : The Pennsylvania State University Press, 2017)
"An annotated and translated collection of instructions on religion, health, sexuality, and family life from the eighteenth-century Moravian Church"--Provided by publisher.
The single sisters' choir -- The single brethren's choir -- The married persons' choir -- The widows' choir.
"This volume consists of the translation of 214 pages of German manuscripts, dated 1785-86, held at the Moravian Archives in Bethlehem, Pennsylvania. The manuscripts, titled 'Instructions for the Choir Helpers, ' are copies of originals held in the Archives of the Unity of the Brethren in Herrnhut, Germany."--Preface.
Includes bibliographical references and index.
Print version record.
Keywords: Moravian Church -- Doctrines -- Early works to 1800.; Moravian Church -- Liturgy -- Texts -- Early works to 1800.; Moravian Archives (Bethlehem, Pa.); Theological anthropology -- Moravian Church -- Early works to 1800.; Human body -- Religious aspects -- Moravian Church -- Early works to 1800.; Pastoral care -- Early works to 1800.; RELIGION / Christianity / Protestant; Electronic books